Predictors of effectiveness of glucagon-like peptide-1 receptor agonist therapy in patients with type 2 diabetes and obesity - Ekaterina V. Tikhonenko; Alina Y. Babenko; Evgeny V. Shlyakhto (Ожирение и метаболизм, 2018)
Background: Type 2 diabetes mellitus (DM2), which mainly develops from visceral obesity, is a socially significant disease. Reduction of losses from DM2 is a priority in modern medicine development. Glucagon-like peptide-1 receptor agonists (aGLP-1) present one of few groups of antidiabetic drugs that allows to reduce not only glycemia, but also weight in DM2. Taking into account predictors of response to the therapy will allow to reach trearment targets with the highest probability, maintaining a safety of treatment, to optimize recommendations for administration of aGPP-1 as much as possible. Aims: To assess dynamics of metabolic parameters, to identify predictors of reduction in blood glucose, body weight and other metabolic parameters on aGLP-1 therapy in patients with DM2 with body mass index (BMI) ≥35 kg/m2. Materials and methods: The study involved 33 patients (10 men, 23 women), who had been treated with aGLP-1, the observation period for 24 weeks was planned. 3 patients terminated the participation before the appointed time (1 – due to pancreatitis development 2 – due to the lack of financial opportunity to purchase the drug). So, 30 patients (10 men, 20 women) were included in the final analysis. Examination consisted of the survey, physical examination with measurement of anthropometric, clinical parameters, filling questionnaires. Data were evaluated at baseline and after 24 weeks of treatment. Results: The study found that patients who achieved weight loss ≥ 5% initially had higher BMI (p = 0.028), lower GLP-1 (p = 0.036), had lower level of ghrelin after standard breakfast test (p = 0.022). There was trend (p = 0.071) to greater decrease in BMI in patients with restrictive type of eating behavior compared to patients who had a mixed type. More pronounced decrease in glycemia was noted in patients who had higher fasting plasma glucose level at inclusion (p = 0.001). Dynamics of HbA1c was better in patients with initially higher GLP-1 (p = 0.016) and higher levels of glycemia (p = 0.001). Also, we revealed the statistically significant decrease in triglycerides level, blood pressure by end of the treatment period. Conclusions: Results indicate the different predictors for reduction in weight, glycemia and blood pressure on aGLP-1 therapy. In addition to the metabolic parameters, level of orexigenic and anorexigenic hormones and psycho-social characteristics of patients help to estimate an expected effect of aGLP-1 therapy. When being identifying, the predictors of weight loss and the predictors of carbohydrate metabolism compensation should be studied separately. Identification of response predictors is necessary to optimize indications for this group of drugs administration in DM2.